The effects of the serum albumin levels at the time of admission on the duration of hospitalization in indirect hyperbilirubinemia (Annals of Medical Research, 2023)
Aim: Indirect hyperbilirubinemia (IHB) is the most common cause of neonatal intensive care unit admissions. Low serum albumin levels are considered to be a risk factor for the development of IHB. We aimed to examine the effect of serum albumin levels during hospitalization on hospital stay in newborns requiring hospitalization due to IHB. Materials and Methods: This retrospective study included 316 newborns. The serum albumin, total bilirubin and bilirubin/albumin ratio were measured at admission for all newborns. The patients were divided into two groups according to the length of hospital stay.Results: Patients hospitalized for longer than 2 days due to IHB were classified as extended hospitalization (Group1) and hospitalization shorter than 2 days (Group2). It was observed that 59 (22.9%) of the patients required hospitalization for more than 2 days due to IHB. The serum albumin levels measured at admission were significantly lower in group 1 (2.92±0.99 gr/dl) and group 2 (3.68±0.35 gr/dl) respectively (p=0.034). The serum albumin level cut off value ≤ 3.55 gr/dl was a good predictive value with a sensitivity of 67.8% and specificity of 76%.Conclusion: The serum albumin level measured at hospitalization can give information about the length of hospital stay. Thus, informing the family about the length of stay at the time of admission to the hospital can reduce the family's anxiety.
Keywords: Hyperbilirubinemia; Serum albumin; Serum bilirubin; Newborn